2011
DOI: 10.1002/jcp.22689
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone utilizes distinct membrane pools of tissue factor to increase coagulation and invasion and these effects are inhibited by TFPI

Abstract: Tissue factor (TF) serving as the receptor for coagulation factor VII (FVII) initiates the extrinsic coagulation pathway. We previously demonstrated that progesterone increases TF, coagulation and invasion in breast cancer cell lines. Herein, we investigated if tissue factor pathway inhibitor (TFPI) could down-regulate progesterone-increased TF activity in these cells. Classically, TFPI redistributes TF-FVII-FX-TFPI in an inactive quaternary complex to membrane associated lipid raft regions. Herein, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Although this is not the first observation that progesterone can regulate PAR1, this is, to our knowledge, the first to demonstrate regulation in breast cancer or mammary glandderived cells. It has not escaped our notice that the timing and mechanism of PAR1 regulation by progesterone is remarkably similar to the progesterone regulation of TF in both T47D and ZR-75 cells (Kato et al 2005b, Quezada et al 2010, Henriquez et al 2011. Advanced breast cancer is associated with a hypercoagulable state that may be triggered or enhanced by the presence of TF and PAR1 on the surface of cancer cells (Ruf & Mueller 2006).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although this is not the first observation that progesterone can regulate PAR1, this is, to our knowledge, the first to demonstrate regulation in breast cancer or mammary glandderived cells. It has not escaped our notice that the timing and mechanism of PAR1 regulation by progesterone is remarkably similar to the progesterone regulation of TF in both T47D and ZR-75 cells (Kato et al 2005b, Quezada et al 2010, Henriquez et al 2011. Advanced breast cancer is associated with a hypercoagulable state that may be triggered or enhanced by the presence of TF and PAR1 on the surface of cancer cells (Ruf & Mueller 2006).…”
Section: Discussionmentioning
confidence: 93%
“…In tumor cells, the factor VIIa-tissue factor (TF) complex activates PAR2 and thereby regulates proangiogenic growth factor expression (Ruf & Mueller 2006). Interestingly, TF is strongly induced by progesterone in both the T47D and ZR-75 breast cancer cell lines (Kato et al 2005b), which in turn increase the procoagulant activity of breast cancer cells (Kato et al 2005b, Henriquez et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this elevated activity of monocyte TF in situ was not related to platelets because it has been observed in their absence (citrated plasma and synthetic coagulation proteome) as well as in their presence (whole blood and synthetic coagulation proteome) . During the last several years, increasing experimental data suggest a role for cell membrane lipid rafts in the modification of TF expression (Fortin et al , 2005 ;Mandal et al , 2006 ;Davizon et al , 2010 ;Henriquez et al , 2011 ) and activity (Sevinsky et al , 1996 ;Dietzen et al , 2004 ;Mandal et al , 2005 ). It has been shown that one of the components of the lipid rafts, cholesterol, might play an important role in TF function (Dietzen et al , 2004 ;Mandal et al , 2005 ) and TF-bearing microparticle shedding (Del Conde et al , 2005 ), although the data related to its effect are contradictory.…”
Section: Tf Environment and Activitymentioning
confidence: 99%
“…Breast cancer progression is dependent on sex steroid hormones. It was previously shown that TF expression increases in response to progesterone exposure [40] , resulting in breast cancer phenotypes via a TF-dependent pathway [41] . Furthermore, a steady state level of TF mRNA in breast cancer cells may be determined by valance of its positive and negative regulatory mechanisms as it was found that PI3K/Akt and MAPK/ERK signaling pathways inversely regulate TF transcript levels in MDA-MB-231 cells [42] .…”
Section: Regulation Of Tf Expression In Breast Cancer Cellsmentioning
confidence: 99%